2019
DOI: 10.1111/tbj.13375
|View full text |Cite
|
Sign up to set email alerts
|

Variables associated with length of stay in patients undergoing mastectomy and delayed‐immediate breast reconstruction with tissue expander

Abstract: Delayed‐immediate reconstruction with the placement of tissue expanders at the time of mastectomy is a common approach to breast reconstruction. The purpose of this study was to identify variables associated with increased LOS in patients that underwent bilateral or unilateral mastectomy with tissue expander placement. Bilateral procedure, a diagnosis of anxiety or depression, and age >55 years were independently associated with increased LOS. More recent year of surgery and Friday surgery were associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…9 Several other groups have since reported their experiences with DI-ABR, either in isolation or in comparison to delayed reconstruction, with varying results. [10][11][12][13] Patients undergoing immediate autologous breast reconstruction (I-ABR) have been shown to experience less psychosocial morbidity than those who have delayed reconstruction due to elimination of the experience of a mastectomy defect. [14][15][16][17] In a previous study by our group, I-ABR had higher rates of volume loss and fat necrosis, but comparable rates of serious complications and the need for revision surgeries when compared with delayed breast reconstruction in patients undergoing PMRT.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…9 Several other groups have since reported their experiences with DI-ABR, either in isolation or in comparison to delayed reconstruction, with varying results. [10][11][12][13] Patients undergoing immediate autologous breast reconstruction (I-ABR) have been shown to experience less psychosocial morbidity than those who have delayed reconstruction due to elimination of the experience of a mastectomy defect. [14][15][16][17] In a previous study by our group, I-ABR had higher rates of volume loss and fat necrosis, but comparable rates of serious complications and the need for revision surgeries when compared with delayed breast reconstruction in patients undergoing PMRT.…”
mentioning
confidence: 99%
“…9 Several other groups have since reported their experiences with DI-ABR, either in isolation or in comparison to delayed reconstruction, with varying results. 10 11 12 13…”
mentioning
confidence: 99%
“…For example, depression and anxiety could be a single group for analysis in one study, and another study might have anxiety, depression, Post-Traumatic Stress Disorder (PTSD), and substance use disorder grouped together as a single entity for analysis. 8,9 This made comparing individual mental illness challenging. The differences in grouping mental illnesses could be due to variability regarding the definition of mental health.…”
Section: Resultsmentioning
confidence: 99%
“…There is variability within the literature regarding whether mental illness affects length of stay (LOS) in general surgery patients. More studies found evidence that MHD increased LOS 8,14,[17][18][19][20][21] than those that did not. 9,22,23 Notably, Paro, et al, found depressed patients had an extended LOS compared to nondepressed patients undergoing surgery for cancer resections (OR 1.41, 95% CI 1.36-1.47), although the authors did not define "extended LOS."…”
Section: Resultsmentioning
confidence: 99%
“…Health care expenditures in the United States have increased at an unprecedented rate over the past decade 1–6. As a result, there is need to identify drivers of increased costs while improving the overall quality of patient care.…”
mentioning
confidence: 99%